The Effect of Problem Based Learning on Understanding of Prospective Elementary School Teacher - Meta Salma Pamenan; Setiawan Edi Wibowo; Haryanto; Ari Wulandari; Ibnu Salam (Universitas Pendidikan Ganesha, 2022)
Most of the understanding of prospective elementary school teachers is still low. This is evidenced by the assignment score of prospective teacher that have not reached the achievement standards set by the university. The PBL model is an effective way to produce important skills such as communication skills, project management, collaborative, and innovative. The purpose of the study was to analyses the effect of the problem based learning method on the level of understanding of prospective elementary school teachers in Indonesia. This study uses quantitative methods with a quasi-experimental design. The experimental design used is the pretest and posttest control group design. Data collection techniques are using the test method. The population and sample in this study consisted of 2 classes majoring in elementary school education. The instrument used in this study was a test, namely pretest and posttest multiple choice questions. The technique used to analyze the data to test the research hypothesis is One Way Anova. Based on the results of this study, it showed that the average posttest value of the experimental class using problem based learning research was 84.82 while the average in the control class was 82.32. There is an increase of 2.5 by using the problem based learning method in Indonesian language lectures. The conclusion is that there is an influence that can increase the understanding of prospective elementary school teachers during the Indonesian language lecture process using the problem based learning method.